The Sarmatian ‘Horseback-riding’ Burial Tradition - Muzaffer Gursoy; Seryk Akylbek; Kopjasar Jetibaev (Documenta Praehistorica, 2020)
The West Kazakhstan region, with its strategic location linking Asia to Europe, has many pasture areas and rivers. These natural factors provided an appropriate environment for human life and contributed to the development of animal husbandry. Throughout history, a great number of horse-mounted nomadic tribes lived in this region. One of these tribes, the Sarmatians, lived in the Iron Age. The Sarmatians were nomadic horsemen and like other steppe tribes were a part of the Kurgan culture. Kurgans have an important place with regard to demonstrating the burial traditions of the Sarmatians. In Kurgan excavations in west Kazakhstan a large number of horseback-riding burials – in which the deceased is positioned as if riding a horse –were found and these are the main subject of our study. Although archaeologists have attributed horseback-riding burials to the Sarmatians, they have not yet made a comment on the meaning of these burials in their belief system. In this study the meaning of these burials will be discussed and related to the belief system by comparing the horseback-riding burials in west Kazakhstan to burials which actually include horses in the Altai region.